HUBUNGAN SOSIAL WARGA PENDATANG DENGAN WARGA TEMPATAN DI DESA BAGAN TUJUH KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Rozalita "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The study is titled social relations with Local Citizens Comer Residents in In The Village Bagan Tujuh District Kunto Darussalam Of Rokan Hulu Regency.Researchers are interested in the theme of this because knowledge Desires, about the social relationships that occur between the citizens of the local residents with newcomers who are intertwined in harmony. To generate a good social relations required a form of interaction that gets a response between individuals with the individual and the individual with the group For the backdrop of ethnic and social relationship, certainly by itself happens to blend individual character in socializing and ultimately very affecting patterns of social relationships that occur in the community. This study aims to describe the interaction-interaction happens on the citizens of local citizens with entrants produce a harmonious Social Relationship. To find out the results of this research, the author then use the technique of collecting data by using the techniques of observation and interviews with respondents. As for the way of sampling or the respondent is done with simple random sampling technique, where a determination of the respondent's done by Expat residents with KK scrambles citizens local as much as the number of respondents 48 people. Researchers conducting a sampling as much as 30% of the total population of 160 families. The theory used in this research is the theory of social interaction as well as forms of social relations. The method used is descriptive quantitative. This research was conducted in the Village Bagan Tujuh District Kunto Darussalam Of Rokan Hulu Regency.The results showed that the social relationships established between the citizens of the local residents with the arrivals of harmonious and good. The results of this study are expected to provide an overview to all those who need information about the Expat Residents social relationships with Local Residents In The Village Bagan Tujuh District Kunto Darussalam Of Rokan Hulu Regency.Key Words: Connection, Local Natives